KEDUDUKAN DAN FUNGSI MASJID AGUNG TERHADAP ALUN-ALUN KOTA MALANG - Ramdlani, Subhan (Journal of Islamic Architecture, 2010)
Identical to any inland cities in Java, Kota Malang also possesses an alun-alun in its downtown, completed with a Jami’ Mosque on the west side. This composition clearly shows some features of capital city’s typology in Java. Beside the similarity, some differences from the typology are also found in Alun-Alun Malang. The composition of Alun-Alun Kota Malang doesn’t put the square as the main orientation of pendopo as the center of the government. Furthermore, the position and function of Jami’ Mosque are dynamically follows the existence of Alun-alun Kota Malang which grows simultaneously with the city development. Thus research about the positional and functional relationships between the Jami’ Mosque and the Alun-Alun needs to be held. A phenomenological approach is used for this research. Primary data is collected through interview with the users, analysts and observers of Alun-Alun in order to grasp an idea of their assumptions about the mosque’s function. Meanwhile, the secondary data is attempted to obtain historical data of Alun-alun Kota Malang, including the establishment and the expansions of Jami’ Mosque, especially when it became Grand Mosque of Kota Malang. The data were compared with the phenomenon which occurs at the moment, the desires and the needs of the user community, as well as the sustainability of function and position the mosque as the identity of alun-alun. The findings of this research are the functions of the Grand Mosque are closely related to the phenomenon of the Alun-Alun’s development.